Evaluation of the Undergraduate Medical Education National Core Curriculum-2014: National Frame of Medical Education in Turkey - (:unkn) unknown (KUWAIT MEDICAL ASSOC, 2018)
Objectives: Transformation experienced in medical education and the unplanned increase in the number of medical faculties has necessitated addressing the issue of medical education on a national level. As a result, at the meeting of the Council of Medical Deans, it was decided that a new national framework for undergraduate medical education should be created. This study aims to evaluate the design/change process and outcomes of the National Core Curriculum-2014 (NCC-2014) for Undergraduate Medical Education. Design: Qualitative study, content analysis Setting: All medical faculties from Turkey Subjects: An expert working group was formed with the participation of 20 academic members from 16 medical faculties and the NCC-2014 was developed by using evaluation meetings and workshops. The design/change process and outcomes of the NCC-2014 were evaluated by national consultations. Data obtained through national consultations were analyzed thematically by three researchers independently. Intervention: None Outcomes and Results: Considering bio-psychosocial/cultural perspective, outcome-based and task-based education, the NCC-2014 was developed in the framework of four fundamental components: The Aim of Medical Education and The Frame of National Competencies with the lists of the Symptoms/Situations, Core Diseases/Clinical Problems and Basic Medical Practices. The frame-program was evaluated positively by the stakeholders due to its providing a perspective aimed at learning, making contribution to the educational standardization of the faculties, being functional and being a guiding light for practitioners. Conclusion: Although the NCC-2014 is the first step towards the standardization of medical education, further planning aimed at internalizing the started change by all relevant institutions should be done.
Keywords: core curriculum; outcome-based education; program evaluation; qualitative analysis; task-based education; LEARNING OUTCOMES; CLINICAL ENVIRONMENT; GUIDE; SCIENCES; CONTEXT